The Embodied Pain Scale - Zha, Zed (Ars Medica, 2025)
As a science, medicine is obsessed with quantifying suffering. But as an art, healthcare delivery must look beyond the one-dimensionality of a pain score. I asked people if they found the numeric pain scale helpful for their medical care on social media. Among the 1,200 people who voted, over 80 percent said "no." Many found the numbers and faces on these scales reductive and harmful. In this visual art piece, I let actual patients define their pain. The usual categorical faces are replaced by dermoscopic photos of my patients' tattoos (with their permission). And the interpretations of them are quotes from people living with chronic pain shared with me online. The result deepens our simplistic understanding of pain.